Management of internet-based service quality - Yan, He, author; Massey, Daniel, advisor; Papadopoulos, Christos, committee member; Pallickara, Shrideep, committee member; Turk, Dan, committee member; Ge, Zihui, committee member; Yates, Jennifer, committee member (Colorado State University. Libraries, 2012)
An increasingly diverse set of services, content distribution network (CDN), Internet games, streaming videos, online-banking, IPTV, VPN, cloud computing and VoIP, are built on top of Internet. For most of these Internet-based services, best effort delivery is no longer an acceptable mode of operation as ultra-high reliability and performance is demanded to meet the stringent service-level requirements. In this dissertation, we focus on the research problem: how to manage the Internet- based service quality in a efficient and proactive manner from a service provider's point of view. Managing Internet-based service quality is extremely challenging due to its massive scale, complicated topology, high protocol complexity, ever-changing software or hardware environment and multiple administrative domains. We propose to look into this problem from two views (user view and network view) and design a novel infrastructure that consists of three systems (Argus, G-RCA and TowerScan) to enable managing Internet-based service quality from both views. We deployed our infrastructure in a tier-1 ISP that provides various Internet-based service and it has proven to be a highly effective way to manage the quality of Internet-based services.